On Microclimatic Islands. The Garden as a Place of Intensified Thermal Experience - Sascha Roesler (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Gardens have always been appreciated as places of particular microclimatic qualities. Seen within the broader context of Enlightenment, gardens can be conceived as places of intensified thermal experience and as man-made concentrations of climate. In the first part, remarks on the aesthetics of microclimates, based on the perception of gardens, will be presented. In times when microclimates were not yet measured by scientific means, the thermal differences found in gardens have already been described as part of poetry and painting or in the treatises of gardeners and botanists. In the second part, the scientification of microclimates and its entanglement with concepts of urban green spaces shall be discussed. Over the course of the 20th century, gardens and green spaces became mitigating measures, fighting severe microclimatic conditions of cities, in particular the so-called urban heat islands. In the third part, the central role of movement in recognizing thermal differences in cities will be highlighted. Two pioneering projects, aiming at exploring the environmental “archipelagos” of cities, will be highlighted. The (garden) cities of Bath (UK) and San Francisco (USA) have been the urban territories for multi-sensorial walks of architect Peter Smithson and landscape architect Lawrence Halprin, both of which took place in 1966. The movement-oriented and body-centred approaches of Smithson and Halprin are historical forerunners of today’s interest in the exploration and cultivation of the microclimatic dynamics of cities and their social and cultural values. Even more than being geometric and spatial entities, microclimates relate directly to the body with its thermal sensations.